The Optimization Model for Interregional Power System Planning considering Carbon Emissions Trading and Renewable Energy Quota Mechanism - Liwei Ju; Zhongfu Tan; Huanhuan Li; Qingkun Tan; Xiangyu Zhang; Wei Zhang (Discrete Dynamics in Nature and Society)
In China, the rapid construction of ultra-high-voltage (UHV) transmission lines promotes interregional resource optimizing configuration and interregional power system planning. This paper analyzes external environment of interregional power system planning from geographical, technical, and policy environments. Then, the paper takes the minimum system investment cost as the optimization objective and constructs the optimization model of interregional power system planning considering carbon emissions trading (CET) and renewable energy quota mechanism (REQ). Finally, this paper sets base scenario, carbon emissions trading scenario, renewable energy quota mechanism scenario, and comprehensive scenario for case simulation. The results show that interregional power system planning could connect power grids in different regions, enlarge wind power consumption space, and relieve the inconformity problem between power resource and load demand. CET and REQ can increase the installed proportion of clean energy and reduce carbon dioxide emissions, but the cost of transmission lines construction and system reserve will increase correspondingly. The optimization effect of REQ on power system planning is better than CET. When they are both introduced, the power structure will reach the best, carbon dioxide emissions will achieve the minimum, and comprehensive benefits will become more balanced.